A computational study to assess the polymorphic landscape of matrix metalloproteinase 3 promoter and its effects on transcriptional activity. (June 2022) - Banik, Payel; Majumder, Ranabir; Mandal, Anik; Dey, Sanjib; Mandal, Mahitosh
Abstract: Background: Matrix metalloproteinase 3 (MMP3) plays a crucial role in cancer progression and development by proteolyzing extracellular matrix substrates. Primarily, the expression of MMP3 is regulated at the transcriptional level. The minute interplay of various transcription factor binding motifs at the promoter region is responsible for the altered expression of the genes. Single nucleotide polymorphism (SNP) at the transcription factor binding sites shows specific effects on gene expressions. Genome-wide association study (GWAS) strongly reported the association of common SNPs (rs3025058, rs522616, and rs617819) of MMP3 promoter with disease progression. The insufficient functional analysis of these promoter SNPs indicates the need for extensive mechanistic analysis on the effects of allelic variants upon transcription factor binding at MMP3 promoter. Methods: The binding of transcription factors on the MMP3 promoter sequence was investigated by a virtual laboratory. The interaction between the specific transcription factor and promoter DNA with allelic variants was analyzed by computational tools. Results: It was found that transcription factor c-Myb and Smad4 binding on MMP3 promoter were altered due to the presence of rs522616 and rs617819 SNPs, respectively. Further, the binding affinity of Smad4 to the MMP3 promoter containing C allele at −375 region is higher than that of its allelic variant G. Conclusion: This study presented that the complex of Smad4-DNA fragment containing C allele has higher binding affinity and stability as compared with its allelic variant. Hence, it is predicted that rs617819 polymorphism directly affects the Smad4 binding motif on MMP3 promoter and alters its gene expression. Highlights: Effects of rs522616 and rs617819 SNPs on MMP3 promoter activity. In silico prediction of transcription factor binding on MMP3 promoter. Transcription factor Smad4 binding on MMP3 promoter containing rs617819. Computational study on effects of rs617819 polymorphic variants on Smad4 binding to its motif at MMP3 promoter.